ANALISIS RASIO PROFITABILITAS DAN AKTIVITAS SEBAGAI DASAR PRNILAIAN KINERJA KEUANGAN PADA PT. ASTRA OTOPARTS Tbk TAHUN 2013-2017 - -, Hadinata Riandah (EKONOMIA, 2018)
This study aims to determine : 1) the financial performance of PT. Astra Otoparts Tbk period 2013-2017 is measured from profitability ratio consisting of Gross Profit Margin, Net Profit Margin and Return On Investment. 2) the financial performance of PT. Astra Otoparts Tbk period 2013-2017 is measured from activity ratio consisting of Receivable Turnover, Inventory turnover and Total assets turnover.The basic theory used is Financial management means planning, oganizng, directing and controlling the financial activtiies such as procurement and utilization of funds of the enterprise, it means applying general management principles to financial resources of the enterprise.The analytical tool used is profitability ratio which consists of Gross Profit Margin, Net Profit Margin dan Return On Investment. And activity ratio which consists of Receivable Turnover, Inventory turnover and Total assets turnover.The results of this study indicate : 1) Gross Profit Margin has increased in 2013 and 2015 and experienced an decreased in 2014, 2016 and 2017. 2) Net Profit Margin has increased in 2013, 2016 and 2017 and experienced an decreased in 2014 and 2015. 3) Return On Investment has increased in 2013, 2016 and 2017 and 2014 and 2015. 4) Receivable Turnover has increased in 2013 and 2016 and experienced an decreased in 2014, 2015 and 2017. 5) Inventory turnover has increased in 2013 and 2016 and experienced an decreased in 2014, 2015 and 2017. 6) Total assets turnover Margin has increased in 2014, 2016 and 2017 and experienced an decreased in 2013 and 2015.